2016
DOI: 10.4025/actasciagron.v38i3.28454
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus as a mitigator of the effects of water stress on the growth and photosynthetic capacity of tropical C4 grasses

Abstract: Water deficiency during the dry seasons influences the relationship between water and gas exchange in tropical grasses, reducing their productive potential. In addition, the phosphorus (P) deficiency Brazilian soils adds to the set of factors limiting crop production. In this context, the objective of this study was to evaluate the responses of different tropical forage species to phosphorus supplementation as mitigating the damage caused by water stress. Seeds of Urochloa brizantha cv. MG-4, Urochloa decumben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…At 30 and 45 DAT, A did not differ between treatments with and without fertilizer; however, a difference did occur at 60 DAT when A was higher in the treatment without fertilizer (Table 2). The A was higher when millet was in a balanced nutritional management, contributing to mitigating water stress and providing rapid initial growth (Kuwahara et al, 2016). By obtaining higher gas exchanges at the beginning of growth, plants that received fertilization completed their cycle in a shorter period than plants without fertilization, justifying the drop in gas exchanges they exhibited at 60 DAT.…”
Section: Resultsmentioning
confidence: 99%
“…At 30 and 45 DAT, A did not differ between treatments with and without fertilizer; however, a difference did occur at 60 DAT when A was higher in the treatment without fertilizer (Table 2). The A was higher when millet was in a balanced nutritional management, contributing to mitigating water stress and providing rapid initial growth (Kuwahara et al, 2016). By obtaining higher gas exchanges at the beginning of growth, plants that received fertilization completed their cycle in a shorter period than plants without fertilization, justifying the drop in gas exchanges they exhibited at 60 DAT.…”
Section: Resultsmentioning
confidence: 99%
“…It is the building block of important macromolecules such as nucleic acids, phospholipids, adenosine triphosphate (ATP). It also takes part in many biochemical reactions and metabolic cycles (Kuwahara et al, 2016). Like total N, P deficiency is often associated with the restriction of plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…P plays an important role in plant biomass allocation and is a structural component of nucleic acids, phospholipids and ATP formation, favoring primary metabolism reactions and constituting ~ 0.2% of plant mass (Kuwahara et al, 2016). For seedling production in Dalbergia nigra Benth., it was found that the addition of 500 mg kg -1 of P favored an increase in biomass (Carlos et al, 2018), similar to the L. alba seedlings in this study (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, P-deficient plants may suffer damage in diffusive and non-diffusive processes of photosynthetic metabolic pathways through a reduction in consumption and regeneration of Rubisco and production of ATP and NADPH (Andrade et al, 2018), which may cause instability in the photochemical process in PS II. Thus, phosphate fertilization is an important agronomic practice since it may assist in photochemical stability (Carstensen et al, 2018) and biomass increases in plants (Kuwahara et al, 2016).…”
mentioning
confidence: 99%